(untitled) (Journal of Plant Disease Sciences, 2018)
Mustard (Brassica juncea L.) is one of the most important oilseed crops grown under a wide range of agro climatic conditions. For its low productivity various diseases have been identified as the important yield destabilizing factors. Biochemical aspects also relates to disease resistance (Shubhangi Mohitkar et al, 2016). Among various diseases of mustard, Powdery mildew is one of the major diseases causing 45 to 90% deduction in mustard grain yield (Hare 1994). Powdery mildew disease is a major constraint for mustard production. However cultivation of resistant variety was considered to be cheap and ecofriendly safe method as compare to chemical control. Keeping this in view efforts have been to find out the sources of resistance against powdery mildew of mustard. Therefore, present study was conducted to screen different varieties against powdery mildew.